Novas faces do trabalho artesanal: as interseções de saberes entre designers de moda e artesãos no interior do Ceará - Silva, Emanuelle Kelly Ribeiro da (2015)
The research sought to understand the new forms of craft production from policy interventions aimed at the development of this activity in Ceará, taking as parameter the exchange of knowledge and practices between artisans and fashion designers under the shares of CEART a as these are sent to the countryside to teach those new work methodology. The overall objective of the study was to understand the interfaces created between the work of fashion designer and craftsman, focusing on the pedagogical interference and methodologies used in the creation and production of the craft process. We tried to erect a reflection based on dialectic, since it allows us to consider the interplay between the observed elements and the constancy of the movement that surrounds them. Thus, the methodology started from a qualitative approach and also the use of ethnographic tools for collecting and analyzing data. The theoretical reference was based on the theories on labor and capitalism in contemporary society; in the study on the design methodologies used today in order to understand their applicability in craft production; Cultural Studies, and; in the discussion of emancipatory education. Exposure of ideas followed the thread of the specific objectives and the presentation of results from them. Thus, some important results were highlighted, such as the contribution of crafts to the current market for the aggregation of cultural value to industrial goods, causing it to be understood as well symbolic / cultural and economic at the same time; the prioritization of the product and not the craftsman needs during interventions, and; the incipient formation of designers working in this area.